Evaluating the impacts of a state led relocation project on beneficiaries' housing satisfactions: Pelican Park as a case study - Mashazhu, Nigel (School of Architecture, Planning and Geomatics, 2017)
The dissertation evaluates the impacts of state relocation projects on beneficiaries housing satisfaction. The government embarks on relocation projects as a means to address massive housing backlog. One of the main drawbacks with relocation projects is locational disadvantage. The broad aim of this dissertation is to evaluate the impacts of a state led relocation project on beneficiary housing satisfaction. The research method employed in the study was the case study based on a state project used for the evaluation process. In order to evaluate beneficiary housing satisfaction, I set an impact assessment criteria specifically (1) enabling mobility; (2) enabling choice; (3) meeting economic needs; (4) meeting physical needs (5) meeting social needs and enabling access to public services; (6); enabling security of tenure; and (7) environmental resilience. The study findings revealed that beneficiaries were highly dissatisfied with their housing. The main driving factor to dissatisfaction was unfavourable location of the settlement which resulted in accessibility challenges to Cape Town central business district, socio-economic opportunities and transport. The relocation process impacted greatly on livelihood strategies of beneficiaries. Beneficiary aspirations were not met. The contribution of the study is not only to unveil the mismatch in state housing projects but also to ensure that future state assisted projects are delivered on quality approach as opposed to quantity approach.